Climate values as predictor of climate change perception in the Kingdom of Saudi Arabia - Arnout, Boshra A. (Frontiers in Psychology, 2022)
Background Understanding public perceptions of climate change and how individuals perceive it is critical to developing effective communication strategies, policies, and socially robust technologies to relieve the risks of climate change. Despite the growing literature on climate change, until now, researchers in Arab countries have not been interested in studying citizens’ perceptions of climate change or identifying the factors that predict it. This study aimed to identify and understand the nature and dynamics of public perceptions of climate change among Arab citizens and detect the level of climate change perception (CCP) and climate values (CV). Also, to detect the predictability of CCP from CV. As well as to reveal the differences between CCP and CV. Methods A random sample consisted of 465 participants (236 male and 229 female), residents of the Kingdom of Saudi Arabia; their ages ranged from 30 years and over. The Climate Change Perception Questionnaire (CCPQ) and Climate Values Questionnaire (CVQ) were applied online. Results The results found average levels of CCP and CV among the study sample. The results also revealed significant statistical differences in the CCP and CV due to gender in favor of females. As well as, there were significant statistical differences in the CCP due to the career field in favor of agriculture, engineering, and construction workers. Also, there were statistical differences in the emotional subscale of climate perception and CV due to age groups in favor of individuals whose ages ranged from 30 to 45 years. The results also found that the CV were a statistically significant predictor (1.2% of total variance) of climate perception. Conclusion The current study showed an average level of CCP and CV among individuals in the Kingdom of Saudi Arabian. The findings also concluded that individuals’ perceptions of climate change are an individual response determined by the individual’s gender, age, and career field and are affected by his values about climate. These findings shed light on the need for climate communications to increase the level of CCP and CV, especially among males and individuals in the age group over 45 years and individuals working in various career fields, whether education, engineering and construction, and commerce and business, etc.; to improve the engagement in mitigation and adaptation measures to climate change.